Linoleic Hydroperoxides Are Potent Hyperoxidative Agents of Sensitive and Robust Typical 2-Cys Peroxiredoxins - Cabrera, Vitória Isabela Montanhero [UNESP]; Vargas, Sabrina [UNESP]; de Medeiros, Nathália Miranda; Sividanes, Gabrielle Nascimento [UNESP]; da Silva, Laura Fernandes [UNESP]; Diniz, Larissa Regina; Alegria, Thiago Geronimo Pires; Lago, João Henrique Ghilardi; Toyama, Marcos Hikari [UNESP]; Miyamoto, Sayuri; Truzzi, Daniela Ramos; Netto, Luis Eduardo Soares; et al. (MDPI, 2025)
Typical 2-Cys peroxiredoxins (2-Cys Prxs, AhpC/Prx1 subfamily) are ubiquitous thiol peroxidases that efficiently reduce H2O2 and other hydroperoxides via a reactive peroxidatic Cys (CP). Under elevated hydroperoxide levels, CP can be hyperoxidized to sulfinic (CP-SO2H) or sulfonic (CP-SO3H) acids, leading to enzyme inactivation. Notably, eukaryotic 2-Cys Prxs are orders of magnitude more sensitive to hyperoxidation (sensitive Prxs) by H2O2 than their bacterial counterparts (robust Prxs). Sensitivity to hyperoxidation also correlates with the catalytic triad composition: enzymes containing threonine (Thr-Prx) are more prone to hyperoxidation by H2O2 than those with serine (Ser-Prx). While hyperoxidation is reversed in eukaryotes by an enzyme (sulfiredoxin), it is generally considered irreversible in bacteria. Here, we compared the hyperoxidation susceptibility of three typical 2-Cys Prxs: human Prx2 (Thr-Prx, sensitive), P. aeruginosa (Thr-Prx, robust) and S. epidermidis (Ser-Prx, robust) to lipid hydroperoxides derived from linoleic acid, containing one or two peroxide moieties per molecule. Employing structural analysis, molecular simulations and kinetic assays, we found that lipid peroxides proved to be potent hyperoxidizing agents for all 2-Cys Prx tested, inactivating the enzymes up to 10,000 times faster than H2O2. These results may have implications for understanding bacterial oxidative stress responses and antimicrobial resistance.